Dinamika Umat Katolik Pada Masa Pandemi Covid-19 di Bali - Sunaryo, Fransiska Dewi Setiowati (Pustaka : Jurnal Ilmu-Ilmu Budaya, 2024)
The COVID-19 pandemic began to unsettle residents in Bali in March 2020. This also has an impact on religious life, especially Catholics in Bali. Prior to the COVID-19 pandemic, Catholics and others were able to worship freely without any restrictions. Everything runs in harmony and solidarity and tolerance between religious communities are maintained. However, since the outbreak of COVID-19, various restrictions have been put in place to prevent transmission to humans in various parts of the world, including in Bali. The purpose of this study was to find out what policies were taken by the Diocese of Denpasar in the face of the COVID-19 pandemic and to find out how Catholics in Bali adapted to the restrictions imposed by the government. The method used in this study is a qualitative descriptive method with a social history approach. In this study, it was concluded that the restrictions in preventing covid-19 did not prevent people from continuing to worship from anywhere and anytime, and religion can be a weapon to strengthen the faith of its people in the face of the covid-19 pandemic.   Pandemi covid-19 mulai meresahkan warga di Bali pada Maret 2020 Hal ini berdampak pula dengan kehidupan umat manusia di berbagai bidang termasuk kehidupan umat beragama di Bali. Sebelum terjadi pandemic covid-19, umat Katolik dan lainnya dapat beribadah dengan leluasa tanpa ada pembatasan. Semua berjalan dengan harmonis serta terjaga solidaritas dan toleransi antar umat beragama. Namun sejak merebaknya covid -19 berbagai pembatasan dilakukan untuk mencegah penularan kepada umat manusia di berbagai belahan dunia, termasuk di Bali. Tujuan dari penelitian ini adalah untuk  mengetahui apa kebijakan yang diambil oleh Keuskupan Denpasar dalam menghadapi pandemic covid-19 dan mengetahui bagaimana umat Katolik di Bali beradaptasi dengan pembatasan yang dilakukan oleh pemerintah. Metode yang digunakan dalam penelitian ini adalah metode deskriptif kualitatif dengan pendekatan sejarah sosial. Dalam penelitian ini diperoleh simpulan bahwa dengan adanya pembatasan dalam pencegahan covid-19 tidak menghalangi umat untuk tetap beribadah dari mana saja dan kapan saja, serta agama dapat menjadi senjata untuk memperkuat keimanan umatnya dalam menghadapi pandemic covid-19.